(untitled) (Педагогіка вищої та середньої школи, 2022)
Tolerance as a social and cultural phenomenon is actualized by significant changes happened recently, which demanded to bring up tolerance culture of a separate person as well as a society in whole. At present time a real possibility has appeared to solve this problem by mastering tolerance culture, understanding the essence of reasons and ways how to accept different trends of thoughts, admitting other people’s right to be different in relationships with the environment.